Sistem Informasi Cuti Pegawai di Badan Pusat Statistik Kota Langsa - Rizalul Akram; Novianda; Seri Rati (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2021)
Limitations regarding the process of applying for employee leave at the Central Bureau of Statistics in Langsa City tend to be ineffective and efficient, so that in the process it makes both employees and leaders feel difficult. In addition to the piles of leave submission files, sometimes forget to process them when an employee applies for leave. The research objective is to produce a web-based leave application program so as to provide convenience to users in applying for and processing leave without always repeating data entry due to operational difficulties. In addition, the time needed is faster and the data entered is more accurate.